Understanding the acute care context to inform palliative care improvements: a qualitative study of hospital-based multidisciplinary clinicians - Claudia Virdun; Gursharan K. Singh; Patsy Yates; Jane L. Phillips; Alison Mudge (BMC Palliative Care)
Abstract Background Population ageing and rising levels of non-communicable diseases are increasing the number of people living with and dying from advanced serious illnesses globally. Many of these people are hospitalised more than once in their last year of life. While there is sound evidence on what patients and their families require for safe and high-quality hospital palliative care, enabling this remains a challenge. This study aimed to understand the clinician, team, and organisational-level barriers and enablers to integrating good palliative care into acute care. Methods An exploratory-descriptive, qualitative study involving semi-structured interviews and practical thematic analysis was conducted. Medical, nursing and allied health disciplines were recruited from three wards (cancer care, mixed general medicine/renal and mixed general medicine/respiratory) within a large Australian metropolitan hospital. Results Eighty-eight interviews (nursing (n = 39); medicine (n = 24); allied health (n = 25)) were undertaken, with a median duration of 25.5 min (range 5 to 55 min). Most participants were female (n = 73, 83%), holding a Bachelor's degree (n = 86, 98%) and ranged from new graduates to participants with over 40 years of post-registration experience. The analysis generated six themes, reflecting the challenges of providing optimal palliative care within acute hospital wards: 1. Understanding when and how to provide palliative care 2. Negotiating shared or changing medical governance in a siloed system 3. Supporting clinicians with the knowledge, skills and confidence to meet palliative care needs 4. Prioritising palliative care amidst the acute care demands of the hospital 5. Optimising the clinical environment to enable private, restful and family-friendly spaces 6. Harnessing organisational support and multidisciplinary clinical leadership Conclusions This study reveals complex, multi-level organisational barriers to integrating palliative care within the acute hospital which will need to be addressed for effective and sustained improvement. Harnessing organisational support and multidisciplinary clinical leadership is key to successful change. Improvements with a focus on developing clinician knowledge, skills, and confidence in palliative care need to pay attention to organisational siloes that constrain shared care, cultures of care that prioritise cure and efficiency, clinical uncertainty in the context of advanced serious illness and optimising the environment for quality palliative care.